Hubungan Social Media Advertising dan Influencer Dalam Pengambilan Keputusan Pembelian Make Up - Jumawan, Jumawan; Edwar, Ratilla Amanda; Shaliha, Fany Lathifatul; Candra, Ayu Nur Jannah Milawati; Makruf, Muhammad Nafis; Nugroho, Muhammad Yusuf (Prisani Cendekia, 2024)
In today's era of innovation and progress, the presence of social media has become a fundamental necessity for various purposes, including the marketing of goods and services. Social media facilitates social interaction and enables dynamic and interactive communication, making it an effective tool in digital marketing. Technological developments have affected many aspects of life, including the business world, where the use of social media helps in marketing and trading strategies. Social media is essential in marketing today. Social Media Marketing (SMM) and influencers play a key role in creating brand awareness and influencing consumer behavior. Qualitative methods were used in the study to understand the relationship between the research variables, focusing on the influence of social media promotion on the purchase decision of beauty products. Collaboration between SMM and influencers is an important strategy in digital marketing, enabling the expansion of brand reach and optimal results in marketing campaigns.